A review of theta oscillation and its functional correlates - Karakaş, Sirel (International journal of psychophysiology, 2020)
Theta is an extensively studied oscillation of the nervous system, but there is only a paucity of reviews on the subject. A review of specifically the cognitive-affective correlates of the theta oscillation is currently unavailable. The present review aims to fill this gap. This review shows that theta-based hippocampal binding brings together the environmentally triggered multimodal elements of episodes or scenes, make multimodal sensory/perceptual and motor processing, facilitatory and inhibitory attention, navigation and episodic memory possible. Hippocampus is centrally located in a selectively distributed theta network. The association between different sources of information and between oscillations of different frequency bands, the connectivity in the theta network and coherences between selected brain areas contribute to the synchrony and hypersynchrony in the human brain. The densely associated pool of information that are represented by the theta oscillation travel over this densely interconnected, and highly synchronized hippocampal-cortical system. In this network, the theta-based cortico-hippocampal interplay produces many cognitive-affective processes, chief one being memory with its encoding, consolidation and retrieval stages. The present review does not make a comparative evaluation of the theta over the evolutionary spectrum; it is focused on the hippocampal-cortical system, and does not consider the subcortical and brain stem structures of the theta network; and among the many different types of memory, treats specifically the episodic memory. Future theta reviews may choose to also treat these issues. Providing a concise exposition of the currently available empirical findings and theoretical formulations, this state-of-the art that review may stimulate research, make new conclusions available, and lead to creative syntheses, allowing a detailed understanding of the contribution of the theta oscillation to the whole-brain work and to the human mind. •A review of specifically the cognitive-affective correlates of the theta oscillation is currently unavailable.•The multimodal elements that make up the episodes and scenes are brought together by the theta-based hippocampal binding.•The pool of information that theta oscillation represents travels over a highly synchronized hippocampal-cortical system.•Theta-based cortico-hippocampal interplay produces many cognitive-affective processes, chief one being memory.